PENGARUH PERBEDAAN PENINGKATAN PERSENTASE PEMBERIAN CACING SUTERA MENURUT UMUR LARVA TERHADAP KELANGSUNGAN HIDUP DAN PERTUMBUHAN LARVA IKAN BAUNG (Hemibagrus nemurus) - Ahmad Syafitra; Agusnimar Agusnimar; Rosyadi Rosyadi (UIR Press, 2018)
This research aims to know the effect of the difference in percentage increase of silkworm by larvae age on the survival and growth of larvae (Hemibagrus nemurus). The method used is experimental method using Completely Random Design (RAL) with 4 treatments and 3 replications namely, P1 (Improvement Percentage 3%, 5% and 7%), P2 (3%, 6% and 9% Percentage increase), P3 (3%, 7% and 11%) P4 (3%, 8% and 13% ). The test fish used were bamboo larvae that were 7 days old with an average weight of 0.0004 gr and an average length of 0.8 cm. Larva fish obtained from the spawning in the Seed Fish Hall (BBI) Faculty of Agriculture, Islamic University of Riau Pekanbaru. The container used is 10 liters or 12 liters water capacity. The result of the research showed the best survival percentage was on P4 treatment, which is 96,00%, followed by P3 treatment that is 94,67%, P2 treatment is 90,67% and lowest is P1, that is 86,67 %. The absolute weight growth and the highest absolute length were at treatment (P4) with weighing 0.30 gr and length 3.35 cm, followed by treatment (P3) that is 0.32 gr and length 3.02 cm, (P2) weighing 0.31 gr and length of 2.84 cm, (P1) weighing 0.30 gr and length 2.77 cm. The highest growth rate of daily weight was also found in treatment (P4), ie 11%, (P3) 10,46%, (P2) 10,24%, and the lowest in treatment (P1) 10,12%.